Adverse Fetomaternal Outcomes In Overweight Pregnant Women - Ijaz, Rimla; Khanam, Faiza; Bareach, Ghanwa; Rasool, Faiza; Sadia, Haleema; Qamar, Semab (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine adverse fetomaternal outcomes in overweight pregnant women. Study Design: Prospective observational study Place and Duration of Study: Department of Gynaecology and Obstetrics, Combined Military Hospital Rawalpindi, Pakistan from Nov 2023 to Apr 2024. Methodology: This study enrolled pregnant women with singleton pregnancy presenting for their first-trimester antenatal visit. Participants were classified into two groups based on body mass index (BMI): the overweight/obese group (Group-A), comprising 75 women with a BMI ≥25 kg/m2, and the normal-weight group (Group-B), consisting of 75 women with a BMI between 18.5-24.9kg/m2. Each participant underwent at least four scheduled assessments during pregnancy to monitor maternal and fetal outcomes. Data were analysed using SPSS version 27.0. Results: The mean age was 28.10 ± 2.96 years. In normal-weight versus overweight/obese women, the outcomes were: cesarean section 25.33% vs. 29.33%, pre-eclampsia 9.33% vs. 25.33%, pregnancy-induced hypertension 12.00% vs. 16.00%, gestational diabetes mellitus 16.00% vs. 12.00%, assisted vaginal delivery 4.00% vs. 1.33%, wound infection 4.00% vs. 5.33%, postpartum hemorrhage 8.00% vs. 5.33%, shoulder dystocia 0.00% vs. 2.67%, stillbirth 0.00% vs. 0.00%, Apgar score ≤7 at one minute 33.33% vs. 13.33%, Apgar score ≤7 at five minutes 20.00% vs. 6.67%, early neonatal death 4.00% vs. 4.00%, and neonatal intensive care unit admissions 24.00% vs. 45.33%. Conclusion: Maternal obesity is significantly associated with adverse maternal and fetal outcomes.